Common errors in the treatment of patients with malignant bone tumors - A. A. Kurilchik; V. E. Ivanov; A. L. Starodubtsev; A. L. Zubarev (Вестник хирургии имени И.И. Грекова)
This study was aimed to analyze the most common diagnostic and therapeutic errors in orthopaedic oncological diseases. Bone tumors usually do not have characteristic symptoms, especially in the early stages of disease development. Therefore, they can often mimic benign tumors and non-tumor diseases. Careful history taking, detailed clinical and X-ray examinations in a timely manner are essential diagnostic tools for patients with bone sarcomas. Moreover, a correct analysis of clinical and radiological findings with regard to the dynamic relationship between them can help make more accurate diagnosis at the first doctor’s visit. Subsequent X-ray examinations performed in oncological centers using special methods such as spiral CТ, MRI, PET/CT with mandatory morphological verification of the diagnosis enable us to make a more precise diagnosis and to provide an objective assessment of pathological processes. The most common diagnostic and therapeutic errors that occur in orthopaedic oncological diseases were analyzed. In 35 % of cases, diagnostic or tactical errors were made by general practitioners. In 15 % of cases, the errors were associated with a latent course of disease and 12 % of cases were wrongly diagnosed as a benign neoplasm.